MANFAAT MEDIA SOSIAL INSTAGRAM SEBAGAI WADAH PROMOSI PADA YUUSTORIES FLORIST DI KARAWANG - Selvy Nur Agustiin; Sekar Ayu Puspitasari; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Marketgram Journal, 2023)
This article discusses the benefits of Instagram social media as a promotional platform for Yuustories Florist in Karawang. Instagram has become an effective platform in expanding brand reach and building interaction with customers. Through a descriptive approach with an observational approach, this visit explores how Yuustories Florist utilizes Instagram to reach the right target market, increase customer engagement, showcase product creativity, and increase sales. The results of this visit show that the use of Instagram provides significant benefits to Yuustories Florist. By utilizing Instagram's features, such as posting attractive images and videos and organizing the feed well, Yuustories Florist managed to increase their brand visibility among Instagram users in Karawang and surrounding areas. In addition, interaction with customers also increased through comments, direct messages, and other interactive features. This helped Yuustories Florist build close relationships with customers and increase brand loyalty. In this article, relevant case studies or proof of success are also presented that show how Yuustories Florist has achieved tangible benefits through comparison of customer engagement, and increased sales achieved by Yuustories Florist